Reação de deslocamento gás-água em catalisadores de platina suportados em TiO2-CeO2 - Cesário, Gabriel (2012)
In this work platinum catalysts supported on CeO2, TiO2, TiO2-CeO2 were prepared for application in water gas shift reaction also called Shift or well known by the letters WGSR - Water Gas Shift Reaction. The mixed titanium dioxide modified with cerium dioxide supports and platinum supported catalysts were obtained by the wet impregnation method, the two supports of titanium dioxide (Degussa and Alfa Aesar) was stabilized by thermal treatment and cerium dioxide support was obtained by thermal decomposition of its precursor. The supports and catalysts were characterized by fluorescence spectroscopy X ray (FRX), X ray diffraction (XRD), the BET method for specific area, CO chemisorption and temperature programmed reduction (TPR). On initial tests the catalysts were activated in situ and tested for WGSR ranging systems that includes the HTS (High Temperature Shift) at 450 350 ° C and LTS (Low Temperature Shift) at 350 200 ° C, and then tested only under LTS conditions. The composition of effluent stream from the reactor was analyzed online by gas chromatograph. It was noted that low charges of cerium oxide is sufficient to enhance the activity and stability of the catalysts supported on mixed oxides when compared with catalysts supported on bare oxides. The effluent stream from the reactor showed compositions similar to those expected when taken into account the ratio H2O/CO. Thus, it was concluded that Pt/Ti-CeO2 is a promising catalyst for application in WGSR reactor.